2008
DOI: 10.1016/j.ydbio.2008.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Polychaetoid controls patterning by modulating adhesion in the Drosophila pupal retina

Abstract: Correct cellular patterning is central to tissue morphogenesis, but the role of epithelial junctions in this process is not well-understood. The Drosophila pupal eye provides a sensitive and accessible model for testing the role of junction-associated proteins in cells that undergo dynamic and coordinated movements during development. Mutations in polychaetoid (pyd), the Drosophila homologue of Zonula Occludens-1, are characterized by two phenotypes visible in the adult fly: increased sensory bristle number an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 80 publications
6
54
0
Order By: Relevance
“…Our observation that NRG and PYD interact to mediate proper sister neurite projections defines a novel role for the ZO-1 homolog PYD in axonogenesis. Thus far, the best-known role of MAGUKs in the nervous system has been in synapse development and function, as is the case for one of the prototypic MAGUKs, Drosophila Discs Large 1 (Dlg1) (Tejedor et al, 1997;Thomas et al, 1997), whereas PYD is known as a component of adherens junctions (Jung et al, 2006;Seppa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that NRG and PYD interact to mediate proper sister neurite projections defines a novel role for the ZO-1 homolog PYD in axonogenesis. Thus far, the best-known role of MAGUKs in the nervous system has been in synapse development and function, as is the case for one of the prototypic MAGUKs, Drosophila Discs Large 1 (Dlg1) (Tejedor et al, 1997;Thomas et al, 1997), whereas PYD is known as a component of adherens junctions (Jung et al, 2006;Seppa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, a-Catenin function has been assessed through RNA interference (RNAi), which does not fully deplete aCatenin (Magie et al, 2002;Cavey et al, 2008;Seppa et al, 2008). These experiments showed that Drosophila a-Catenin is required for AJ function and integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Third instar eye of gmr-Gal4 crosses were dissected and the histology was performed as previously described (Seppa et al, 2008). Expression was detected by confocal (Zeiss) using anti-HA (Roche, 1:200; 2 antibody anti-rat568 (1:250)) or antiserum raised against the CGb subunit (1:1500; 2 antibody ant-rabbit 488 (1:250)).…”
Section: Immunohistochemistry Antibodies and Semmentioning
confidence: 99%